2016
DOI: 10.1128/aem.01914-16
|View full text |Cite
|
Sign up to set email alerts
|

Minor Coat and Heat Shock Proteins Are Involved in the Binding of Citrus Tristeza Virus to the Foregut of Its Aphid Vector, Toxoptera citricida

Abstract: Vector transmission is a critical stage in the viral life cycle, yet for most plant viruses how they interact with their vector is unknown or is explained by analogy with previously described relatives. Here we examined the mechanism underlying the transmission of citrus tristeza virus (CTV) by its aphid vector, Toxoptera citricida, with the objective of identifying what virus-encoded proteins it uses to interact with the vector. Using fluorescently labeled virions, we demonstrated that CTV binds specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 33 publications
0
37
0
1
Order By: Relevance
“…It is not presently known how this diversity, particularly in the p27, p65 and p61 genes, affects transmission efficacy of individual isolates. It has recently been demonstrated [10] that this virus uses three proteins to interact with the lining of the cibarium of the aphid: (1) p27, the minor coat protein, which has been reported to be involved in vector interaction in other characterized closteroviruses [11,12], (2) p65, a HSP70like molecular chaperone, and (3) p61, a HSP90-like molecular chaperone, both of which are required for virion assembly [13].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…It is not presently known how this diversity, particularly in the p27, p65 and p61 genes, affects transmission efficacy of individual isolates. It has recently been demonstrated [10] that this virus uses three proteins to interact with the lining of the cibarium of the aphid: (1) p27, the minor coat protein, which has been reported to be involved in vector interaction in other characterized closteroviruses [11,12], (2) p65, a HSP70like molecular chaperone, and (3) p61, a HSP90-like molecular chaperone, both of which are required for virion assembly [13].…”
mentioning
confidence: 99%
“…Having determined that FS577 was transmitted at significantly greater frequency than T36, or its infectious clone, we constructed a series of hybrid infectious clones between the two isolates. As previous research had shown that the p65, p61, and p27 genes are involved in the interaction between virus and aphid [10], we focused on these genes. First, a single replacement from within p6 to within p18 (bases 11661 to 17300) was constructed through amplification (Table 1) of a fragment from FS577-1-8 cDNA, and substituted into the T36 infectious clone [15] using PmeI-PstI restriction sites.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the viral determinant (s) and specific virion retention sites underlying the mechanism of LIYV transmission has provided insights into the NCSP transmission processes and paved the way for similar investigations of other NCSP criniviruses (Ng, unpublished) [10]. Recently, Killiny et al [11] performed VR assays in which aphid vectors were fed purified CTV virions tagged with the green fluorescent protein (GFP) and found GFP signals retained within the vectors' foreguts. In in vitro competitive binding assays where the dissected foreguts of aphid vectors were co-incubated with specific CTV proteins and the GFP-tagged virions, three of the capsid proteins, CPm, P61 and P65, significantly reduced the virion-associated GFP fluorescence in the vectors' foreguts, suggesting that these proteins played a role in mediating specific virion retention in the aphid vector.…”
Section: Direct Influences On Ncsp Virus Transmission Viral Determinamentioning
confidence: 99%